Streptococcus pneumoniae: 'captain of the men of death' and financial burden. Issue 12 (2nd December 2022) - Yesilkaya, Hasan; Oggioni, Marco R.; Andrew, Peter W.
Abstract : Streptococcus pneumoniae may inhabit the upper respiratory tract of humans without causing harm but it also causes diseases with high morbidity and mortality. It has excellent adaptive capabilities thanks to its ability to shuffle its genetic content by acquiring and incorporating DNA from other bacteria and is highly competent for genetic transformation. Sugar sensing, cleavage and transport ensure its fitness and survival in the host, and intracellular survival in macrophages has been linked to virulence. The polysaccharide capsule and toxin pneumolysin are the most important virulence determinants. Polysaccharide-based vaccines provide protection against the serotypes represented in vaccine formulations.